Using a Bootstrap Approach to Rate the Raters - André Güttler (Johann Wolfgang Goethe-Universität Frankfurt am Main, Fachbereich Wirtschaftswissenschaften, 2004)
This paper compares the accuracy of credit ratings of Moody's and Standard&Poor's. Based on 11,428 issuer ratings and 350 defaults in several datasets from 1999 to 2003 a slight advantage for the rating system of Moody's is detected. Compared to former research the robustness of the results is increased by using nonparametric bootstrap approaches. Furthermore, robustness checks are made to control for the impact of Watchlist entries, staleness of ratings and the effect of unsolicited ratings on the results.
Keywords: G23; G15; 330; Credit rating agencies; Validation; Bootstrap; Kreditwürdigkeit; Auskunftei; Statistischer Test; Schätzung; Vergleich; Vereinigte Staaten; Ratingagentur; Validitäts; Moody's Investors Service New York; NY; Standard and Poor's Corporation New York; NY